The influence of competence and motivation on employee performance in the Payakumbuh Sub-District office of West Sumatra, Limapuluh Regency, West Sumatra City - Hamsal; Eva Sundari; Iyoyo Dianto; Imam Hanafi; Muhammad Arif; Fadli Hamzah (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This research aims to analyze the impact of competence and work motivation on employee performance at the Payakumbuh District Office, West Sumatra, Kabupaten Lima Puluh Kota. Research Methodology: This study employs a quantitative approach using a descriptive survey method. The research population includes 47 employees at the Payakumbuh District Office. The collected data were analyzed using Smart Partial Least Square (PLS). Results: Competence and work motivation both have a positive and significant effect on employee performance, with t-values of 3.818 and 2.703 (p < 0.05). The adjusted R² of 56.2% shows that these two variables collectively explain more than half of the variance in employee performance. Conclusions: Competence and motivation significantly enhance employee performance, with competence having the strongest effect. Strengthening both factors is vital to improve effectiveness and public service quality. Limitations: The study's population is limited to employees at the Payakumbuh District Office, which may restrict the generalizability of the findings to other government institutions. Contribution: Nevertheless, this research significantly contributes to human resource management, particularly within the governmental context.